PENGARUH KINERJA AKUNTANSI TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2014 - Handoko, Fery Handoko; T, Sutrisno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to examine the effect of accounting performance indicators represented by the variable earnings per share, price to book value, and price earnings ratio on stock returns. The sample was a manufacturing company in the list of the Stock Exchange during January 2010 to December 2014, a company that has always consistently deliver its financial statements on a regular basis and have the completeness of financial data in accordance with what is needed in this study, which is consistent company has an equity value positive during the period of observation that in 2010 through 2014, and the company always consistently make a profit on that observation period of 2010 through 2014. Based on these criteria the sample used in this study is 62 companies. Methods of research conducted with the method of multiple linear regression, t-test and F test results showed a partial earnings per share significant effect on stock returns, while price to book value, and price earnings ratio not significant effect on return stock. Simultaneously, earnings per share, price to book value, and price earnings ratio have a significant effect on stock returns Keywords: Stock return, earning per share (EPS), price to book value (PBV), price earning ratio (PER)